Resin composition, insulating resin cured body, laminate and circuit board
The resin composition, featuring a thermosetting resin, specific inorganic filler particles, and an ion trapping agent, addresses the insulation reliability challenges of metal-based circuit boards under high temperature and DC high voltage, enhancing productivity and preventing solder cracks.
Patent Information
- Application Number
- JP2023172910
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Ceramic circuit boards face issues with solder cracks during heat cycles and require improved insulation reliability under high temperature and DC high voltage conditions, which metal-based circuit boards need to address.
A resin composition comprising a thermosetting resin, an inorganic filler with a combination of flaky and cohesive particles, and an inorganic ion trapping agent, which forms an insulating layer with enhanced insulation reliability under high temperature and DC high voltage conditions.
The resin composition effectively forms an insulating layer with superior insulation reliability against DC high voltage under high temperature conditions, suppressing solder cracks and improving productivity compared to ceramic circuit boards.
Smart Images

Figure 2025063576000005 
Figure 2025063576000006 
Figure 2025063576000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition that is suitably used for producing an insulating layer of a circuit board (metal-based circuit board), a cured insulating resin, a laminate, and a circuit board. [Background technology]
[0002] A variety of circuit boards have been put to practical use as circuit boards on which electronic and electrical components such as semiconductor elements are mounted to form hybrid integrated circuits. Circuit boards are classified based on the board material into resin circuit boards, ceramic circuit boards, metal-based circuit boards, etc.
[0003] Resin circuit boards are inexpensive, but because the thermal conductivity of the board is low, their applications are limited to those requiring relatively low power. Ceramic circuit boards, due to the characteristics of ceramics, such as high electrical insulation and heat resistance, are suitable for applications requiring relatively high power, but have the disadvantage of being expensive. On the other hand, metal-based circuit boards have intermediate properties between the two, and are suitable for general-purpose applications requiring relatively high power, such as inverters for refrigerators, inverters for commercial air conditioners, power sources for industrial robots, and power sources for automobiles.
[0004] For example, Patent Document 1 discloses a method for obtaining a circuit board having excellent stress relaxation properties, heat resistance, moisture resistance, and heat dissipation properties by using a composition for circuit boards containing a specific epoxy resin, a curing agent, and an inorganic filler as essential components. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-266533 A Summary of the Invention [Problem to be solved by the invention]
[0006] If ceramic circuit boards could be substituted for metal-based circuit boards, it is expected that productivity would improve. Ceramic circuit boards also have the issue that solder cracks are likely to occur on the board during heat cycles, but by substituting metal-based circuit boards, it is expected that the occurrence of solder cracks will be suppressed. Meanwhile, since ceramic circuits are suited to applications that require relatively large amounts of power, when substituting metal-based circuit boards for ceramic circuit boards, there is a demand for improved insulation reliability against the application of high DC voltages (especially insulation reliability under high temperature conditions) for the metal-based circuit boards.
[0007] Therefore, an object of the present invention is to provide a resin composition capable of forming an insulating layer having excellent insulating reliability against application of a high DC voltage under high temperature (150° C.) conditions, and to provide an insulating resin cured product which is a cured product of the resin composition, and a laminate and a circuit board using the insulating resin cured product. [Means for solving the problem]
[0008] The present invention includes the following [1] to
[13] . [1] A composition comprising a thermosetting resin, an inorganic filler, and an inorganic ion scavenger, the inorganic filler includes first particles which are scaly particles and second particles which are agglomerates of the scaly particles, a content of the first particles is 1 vol% or more and 60 vol% or less with respect to a total content of the first particles and the second particles, A resin composition, wherein the content of the inorganic ion scavenger is 0.1 to 50 mass % based on the total amount of the thermosetting resin. [2] The resin composition according to [1], wherein the first particles have an average aspect ratio of 1 to 200, and the second particles have an average aspect ratio of 1 to 2. [3] The first particles are boron nitride particles, and in an X-ray diffraction measurement, the ratio I(002) / I(100) of the peak intensity I(002) of the (002) plane to the peak intensity I(100) of the (100) plane is 50 to 1000; The resin composition according to [1] or [2], wherein the second particles are boron nitride particles, and a ratio I(002) / I(100) of a peak intensity I(002) of the (002) plane to a peak intensity I(100) of the (100) plane in an X-ray diffraction measurement is 1 to 20. [4] The resin composition according to any one of [1] to [3], wherein a ratio of an average particle size of the first particles to an average particle size of the second particles is 1.5 or more and 20 or less. [5] The resin composition according to any one of [1] to [4], wherein a ratio of an average aspect ratio of the first particles to an average aspect ratio of the second particles is 0.01 or more and 0.8 or less. [6] The resin composition according to any one of [1] to [5], wherein the inorganic filler has a thermal conductivity of 20 W / m·K or more. [7] The resin composition according to any one of [1] to [6], wherein the content of the inorganic filler is 30 to 70 volume % based on the total volume of the resin composition. [8] The resin composition according to any one of [1] to [7], wherein the inorganic ion scavenger contains both an anion exchanger and a cation exchanger, or both ion exchangers. [9] The resin composition according to any one of [1] to [8], wherein the inorganic ion scavenger contains at least one selected from the group consisting of Al, Mg, Bi, Zr, Sb, and Zn.
[10] The resin composition according to any one of [1] to [9], wherein the inorganic ion scavenger contains at least one selected from the group consisting of Bi, Zr, Sb, and Zn.
[11] The resin composition according to any one of [1] to
[10] , which has a peak in the range of 2θ=11 to 15° in X-ray diffraction measurement.
[12] The resin composition according to any one of [1] to
[11] , wherein the thermosetting resin is an epoxy resin.
[13] Further comprising a copolymer, The resin composition according to any one of [1] to
[12] , wherein the copolymer has (meth)acrylic monomer units A having an anionic group, (meth)acrylic monomer units B having a cationic group, and (meth)acrylic monomer units C other than the (meth)acrylic monomer units A and the (meth)acrylic monomer units B.
[14] A cured insulating resin product, which is a cured product of the resin composition according to any one of [1] to
[13] .
[15] A semiconductor device comprising: a first metal layer; an insulating layer disposed on one surface of the first metal layer; and a second metal layer disposed on a surface of the insulating layer opposite to the first metal layer; The insulating layer is the insulating resin cured body according to
[14] .
[16] A semiconductor device comprising: a metal layer; an insulating layer disposed on one surface of the metal layer; and a metal circuit portion disposed on a surface of the insulating layer opposite to the metal layer; The circuit board, wherein the insulating layer is the insulating resin cured body according to
[14] . Effect of the Invention
[0009] According to the present invention, there is provided a resin composition capable of forming an insulating layer having excellent insulating reliability against application of a high DC voltage under high temperature (150° C.) conditions. Also, according to the present invention, there are provided an insulating resin cured product which is a cured product of the resin composition, and a laminate and a circuit board using the insulating resin cured product. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view showing one embodiment of a laminate. [Diagram 2] FIG. 2 is a cross-sectional view illustrating an embodiment of a circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Preferred embodiments of the present invention will now be described in detail.
[0012] One embodiment of the present invention is a resin composition containing a thermosetting resin, an inorganic filler, and an inorganic ion scavenger.
[0013] Examples of the thermosetting resin include silicone resin, epoxy resin, phenol resin, cyanate resin, melamine resin, urea resin, thermosetting polyimide resin, and unsaturated polyester resin. The thermosetting resin may include an epoxy resin. The thermosetting resin may be used alone or in combination of two or more kinds.
[0014] The content of the thermosetting resin may be 10% by mass or more, 20% by mass or more, or 25% by mass or more, based on the total mass of the resin composition, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under a high temperature (150° C.) condition. The content of the thermosetting resin may be 50% by mass or less, 40% by mass or less, or 30% by mass or less, based on the total mass of the resin composition, from the viewpoint of improving thermal conductivity.
[0015] The resin composition contains an inorganic filler. The inorganic filler may be, for example, a known inorganic filler used in applications requiring insulation and thermal conductivity (excluding inorganic ion scavengers described below). The inorganic filler may contain, for example, one or more selected from the group consisting of aluminum oxide (alumina), silicon oxide, silicon nitride, boron nitride, aluminum nitride, and magnesium oxide, and from the viewpoint of further improving insulation reliability in a high humidity environment, may contain one or more selected from the group consisting of aluminum oxide, silicon oxide, silicon nitride, boron nitride, and aluminum nitride, and may contain one or more selected from the group consisting of aluminum oxide, boron nitride, and aluminum nitride.
[0016] The inorganic filler includes first particles, which are scaly particles, and second particles, which are aggregated particles of the scaly particles. The inorganic filler may include particles (third particles) that do not fall under the first particles and second particles. The content of the first particles is 1 volume % or more and 60 volume % or less with respect to the total content of the first particles and the second particles.
[0017] The inorganic filler contains first particles, which are scale-like particles, and second particles, which are aggregated particles of the scale-like particles, and the content of the first particles is 1 volume % or more and 60 volume % or less with respect to the total content of the first particles and the second particles, so that a resin composition capable of forming an insulating layer having excellent insulating reliability against application of a high direct current voltage under high temperature (150°C) conditions is easily obtained. The present inventors speculate on the reason for this as follows. That is, the inorganic filler contains a plurality of particles with different shapes, so that the filling property of the inorganic filler is improved and the movement of ions that affect the insulating property is easily restricted. In addition, the presence of a certain content of the second particles, which have a relatively complex shape, makes it easy to sufficiently restrict the movement of ions that affect the insulating property. As a result, the movement of ions in the resin composition is restricted, and the ions are easily captured by the inorganic ion scavenger, so that it is speculated that the insulating property of the insulating layer formed by the resin composition is improved. However, the mechanism of the present invention is not limited to the above reasons.
[0018] The first particles and the second particles may each contain the same component or different components. For example, the first particles and the second particles may each be boron nitride particles. The second particles may be agglomerated particles of the first particles, or agglomerated particles of scaly particles different from the first particles. In this specification, the agglomerated particles refer to agglomerated particles in which a plurality of particles are in contact with each other to form a lump-like particle.
[0019] The particle diameter of the first particles may be 50 μm or less, 30 μm or less, 15 μm or less, 10 μm or less, or 8 μm or less from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150° C.) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85° C., 85% RH) conditions, and from the same viewpoint, may be 0.1 μm or more, 1 μm or more, 3 μm or more, or 5 μm or more. The particle diameter of the first particles is obtained by embedding the first particles in a resin, preparing a sample for cross-sectional observation by mechanical polishing and ion milling treatment, depositing gold plating on the sample, and then measuring the maximum length of the particles when observing the particles at a magnification of 10,000 times with a scanning electron microscope (SEM).
[0020] The average particle diameter of the first particles may be 50 μm or less, 30 μm or less, 15 μm or less, 10 μm or less, or 8 μm or less from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150° C.) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85° C., 85% RH) conditions, and from the same viewpoint, may be 0.1 μm or more, 1 μm or more, 3 μm or more, or 5 μm or more. The average particle diameter of the first particles is obtained by measuring the maximum length of each of 10 first particles in one visual field during observation with an SEM in the above-mentioned method for measuring the particle diameter of the first particles, and averaging them.
[0021] From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85% RH) conditions, the aspect ratio of the first particles may be 1 to 200, 5 to 200, 10 to 200, or 50 to 150. The aspect ratio of the first particles is obtained by measuring the maximum length and maximum thickness of the first particles and dividing the maximum length by the maximum thickness in the above-mentioned method for measuring the particle size of the first particles.
[0022] From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85%RH) conditions, the average aspect ratio of the first particles may be 1 to 200, 5 to 200, 10 to 200, or 50 to 150. The average aspect ratio of the first particles is obtained by measuring the maximum length and maximum thickness of each of 10 first particles in one visual field during observation with an SEM in the above-mentioned method for measuring the particle size of the first particles, and dividing the maximum length by the maximum thickness and averaging the results.
[0023] When the first particles include boron nitride particles (first boron nitride particles), the ratio I(002) / I(100) of the peak intensity I(002) of the (002) plane to the peak intensity I(100) of the (100) plane in X-ray diffraction measurement of the first boron nitride particles may be 50 to 1000, 60 to 800, 70 to 600, 80 to 400, or 90 to 200.
[0024] The particle diameter of the second particles may be larger than the particle diameter of the first particles, and may be more than 8 μm, more than 10 μm, more than 15 μm, more than 30 μm, or more than 50 μm. The particle diameter of the second particles may be 500 μm or less, 300 μm or less, 200 μm or less, 150 μm or less, or 100 μm or less. The particle diameter of the second particles is obtained by embedding the second particles in a resin, preparing a sample for cross-sectional observation by mechanical polishing and ion milling, depositing gold plating on the sample, and then measuring the maximum length of the particles when observing the particles at a magnification of 1,000 times with a scanning electron microscope (SEM).
[0025] The average particle size of the second particles may be larger than the average particle size of the first particles, and may be more than 8 μm, more than 10 μm, more than 15 μm, more than 30 μm, or more than 50 μm. The average particle size of the second particles may be 500 μm or less, 300 μm or less, 200 μm or less, 150 μm or less, or 100 μm or less. The average particle size of the second particles can be measured using a laser diffraction / scattering & dynamic image analysis type particle size distribution / particle shape measuring device.
[0026] The aspect ratio of the second particles may be 1 to 5, 1 to 4, 1 to 3, or 1 to 2. The aspect ratio of the second particles can be obtained by measuring the maximum length of the second particles and the maximum length in a direction perpendicular to the direction of the maximum length, and dividing the maximum length by the maximum length in the direction perpendicular to the direction of the maximum length, in the above-mentioned method for measuring the particle diameter of the second particles.
[0027] The average aspect ratio of the second particles may be 1 to 5, 1 to 4, 1 to 3, or 1 to 2. The average aspect ratio of the second particles can be measured using a laser diffraction / scattering & dynamic image analysis type particle size distribution / particle shape measuring device.
[0028] When the second particles include boron nitride particles (second boron nitride particles), the ratio I(002) / I(100) of the peak intensity I(002) of the (002) plane to the peak intensity I(100) of the (100) plane in X-ray diffraction measurement of the second boron nitride particles may be 1 to 20, 1 to 15, 1 to 10, 1 to 5, 1.1 to 4, 1.2 to 3, or 1.2 to 2.
[0029] The ratio of the average particle diameter of the first particles to the average particle diameter of the second particles (average particle diameter of the second particles / average particle diameter of the first particles) may be 1.5 or more, 2 or more, 3 or more, 4 or more, or 5 or more from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature (150 ° C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature and high humidity (85 ° C, 85% RH) conditions, and from the same viewpoint, it may be 20 or less, 15 or less, 10 or less, 8 or less, or 6 or less. The ratio of the average particle diameter of the first particles to the average particle diameter of the second particles may be 1.5 or more and 20 or less, or 3 or more and 10 or less.
[0030] The ratio of the average aspect ratio of the first particles to the average aspect ratio of the second particles (average aspect ratio of the second particles / average aspect ratio of the first particles) may be 0.01 or more, 0.05 or more, 0.1 or more, 0.15 or more, or 0.18 or more from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature (150 ° C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature and high humidity (85 ° C, 85% RH) conditions, and from the same viewpoint, it may be 0.8 or less, 0.6 or less, 0.4 or less, 0.3 or less, or 0.2 or less. The ratio of the average aspect ratio of the first particles to the average aspect ratio of the second particles may be 0.01 or more and 0.8 or less, or 0.1 or more and 0.4 or less.
[0031] The inorganic filler may have multiple peaks in the particle size distribution curve. The inorganic filler may include, for example, a first particle group having a peak in the range of 0.1 μm to 15 μm in the particle size distribution curve, and a second particle group having a peak in the range of more than 15 μm to 300 μm in the particle size distribution curve. In this specification, having a peak in a specific range in the particle size distribution curve means that the peak top is present in a specific range.
[0032] The first particle group may have a single peak or multiple peaks in the range of 0.1 μm to 15 μm in the particle size distribution curve. The second particle group may have a single peak or multiple peaks in the range of more than 15 μm to 300 μm in the particle size distribution curve.
[0033] From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85% RH) conditions, the first particle group may have a peak in a particle size distribution curve in a range of 0.1 μm or more, 0.5 μm or more, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 5 μm or more, and from the same viewpoint, may have a peak in a range of 15 μm or less, 12 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, or 7 μm or less.
[0034] From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85% RH) conditions, the second particle group may have a peak in a particle size distribution curve in a range of more than 15 μm, more than 20 μm, more than 25 μm, more than 30 μm, more than 35 μm, or more than 40 μm, and from the same viewpoint, may have a peak in a range of 300 μm or less, 250 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 80 μm or less, 60 μm or less, or 50 μm or less.
[0035] In the particle size distribution curve, the difference between the position of the peak of the first particle group and the position of the peak of the second particle group ((position of the peak of the second particle group) - (position of the peak of the first particle group)) may be 10 μm or more, 20 μm or more, or 30 μm or more from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against DC high voltage application under high temperature (150 ° C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against DC high voltage application under high temperature and high humidity (85 ° C, 85% RH) conditions, and from the same viewpoint, it may be 200 μm or less, 150 μm or less, 100 μm or less, or 50 μm or less. The difference between the position of the peak of the first particle group and the position of the peak of the second particle group may be 10 μm or more and 200 μm or less, or 20 μm or more and 100 μm or less.
[0036] The thermal conductivity of the inorganic filler may be 20 W / m·K or more, 50 W / m·K or more, 100 W / m·K or more, or 150 W / m·K or more, and may be 3500 W / m·K or less, 2000 W / m·K or less, 600 W / m·K or less, 300 W / m·K or less, or 200 W / m·K or less. The thermal conductivity of the first particles may be within the above range, and the thermal conductivity of the second particles may be within the above range.
[0037] The content of the first particles may be 2% by volume or more, 3% by volume or more, 5% by volume or more, 8% by volume or more, or 10% by volume or more, based on the total content of the first particles and the second particles, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85%RH) conditions, and from the same viewpoint, it may be 50% by volume or less, 40% by volume or less, 30% by volume or less, 20% by volume or less, or 15% by volume or less. The content of the first particles may be 1% by volume or more and 50% by volume or less, 3% by volume or more and 30% by volume or less, 3% by volume or more and 30% by volume or less, or 5% by volume or more and 20% by volume or less, based on the total content of the first particles and the second particles.
[0038] The content of the second particles may be 50% by volume or more, 60% by volume or more, 70% by volume or more, 80% by volume or more, or 85% by volume or more, based on the total content of the first particles and the second particles, from the viewpoint of being able to easily obtain a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of being able to easily obtain a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85%RH) conditions, and from the same viewpoint, may be 99% by volume or less, 97% by volume or less, 95% by volume or less, 92% by volume or less, or 90% by volume or less. The content of the second particles may be 50% by volume or more and 99% by volume or less, 60% by volume or more and 97% by volume or less, or 70% by volume or more and 95% by volume or less, based on the total content of the first particles and the second particles.
[0039] From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85% RH) conditions, the total content of the first particles and the second particles may be 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, or 95 mass% or more, or may be substantially 100 mass%, relative to the total mass of the inorganic filler.
[0040] The total content of the first particles and the second particles may be 50 vol% or more, 60 vol% or more, 70 vol%, 80 vol% or more, 90 vol% or more, or 95 vol% or more, relative to the total volume of the inorganic filler, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having better insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having better insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85% RH) conditions.
[0041] The content of the inorganic filler may be 30% by mass or more, 40% by mass or more, 50% by mass or more, or 60% by mass or more, based on the total mass of the resin composition, from the viewpoint of improving thermal conductivity. The content of the inorganic filler may be 80% by mass or less, 75% by mass or less, 70% by mass or less, or 65% by mass or less, based on the total mass of the resin composition, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high-voltage direct current under high-temperature (150°C) conditions, and is preferably 65% by mass or less, based on the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high-voltage direct current under high-temperature and high-humidity (85°C, 85%RH) conditions.
[0042] The content of the inorganic filler may be 20% by volume or more, 30% by volume or more, 40% by volume or more, 45% by volume or more, or 50% by volume or more, based on the total volume of the resin composition, from the viewpoint of improving thermal conductivity. The content of the inorganic filler may be 80% by volume or less, 70% by volume or less, 60% by volume or less, 55% by volume or less, or 50% by volume or less, based on the total volume of the resin composition, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high-voltage direct current under high-temperature (150°C) conditions, and is preferably 55% by volume or less, based on the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high-voltage direct current under high-temperature and high-humidity (85°C, 85%RH) conditions. The content of the inorganic filler may be 20 to 80% by volume or 30 to 70% by volume, based on the total volume of the resin composition.
[0043] An inorganic ion trapping agent is an inorganic material that has the function of trapping at least one of cations and anions (has ion trapping properties). In this specification, "ion trapping properties" refers to the property of adsorbing the ions to be trapped onto the surface of an inorganic material, or the property of introducing the ions to be trapped into the structure of an inorganic material by ion exchange between the ions in the structure of the inorganic material and the ions to be trapped. Examples of ions to be trapped by an inorganic ion trapping agent include cations such as Na ions, Cu ions, and Ag ions; and anions such as Cl ions and Br ions.
[0044] The inorganic ion trapping agent may contain at least one selected from the group consisting of Al, Mg, Bi, Zr, Sb, and Zn, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature (150°C) conditions, and may contain at least one selected from the group consisting of Bi, Zr, Sb, and Zn, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85%RH) conditions. The inorganic ion trapping agent may be, for example, an oxide, an acid chloride, or a hydrate thereof containing at least one of these metal elements. The inorganic ion trapping agent may contain two or more of these metal elements.
[0045] Examples of inorganic ion trapping agents include anion exchangers that trap anions, cation exchangers that trap cations, and both ion exchangers that trap both anions and cations. The inorganic ion trapping agents may be used alone or in combination of two or more types, and for example, both ion exchangers may be a mixture of anion exchanger and cation exchanger. From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having excellent insulating reliability against application of a high direct current voltage under high temperature and high humidity (85°C, 85% RH) conditions, the inorganic ion trapping agent may contain both anion exchanger and cation exchanger, or both ion exchangers.
[0046] The anion exchanger may be an inorganic material containing at least one selected from the group consisting of Al, Mg, Bi, Zr, and Zn. Specific examples of the anion exchanger include IXE-500 (Bi-based), IXE-530 (Bi-based), IXE-550 (Bi-based), IXE-700 (Mg, Al-based), IXE-700F (Mg, Al-based), IXE-770 (Mg, Al-based), IXE-770D (Mg, Al-based), IXE-702 (Al-based), IXE-800 (Zr-based), and IXE-1000 (Zn-based) (all manufactured by Toagosei Co., Ltd.).
[0047] The cation exchanger may be an inorganic material containing at least one selected from the group consisting of Zr, Sn, and Ti. Specific examples of the cation exchanger include IXE-100 (Zr-based), IXE-200 (Sn-based), IXE-300 (Sb-based), and IXE-400 (Ti-based) (all manufactured by Toagosei Co., Ltd.).
[0048] The ion exchangers include inorganic materials containing at least one selected from the group consisting of Al, Mg, Bi, Zr, and Sb. Specific examples of the ion exchangers include IXE-1320 (Mg, Al-based), IXE-600 (Sb, Bi-based), IXE-633 (Bi-based), IXE-680 (Bi-based), IXE-6107 (Zr, Bi-based), IXE-6136 (Zr, Bi-based), IXEPLAS-A1 (Zr, Mg, Al-based), IXEPLAS-A2 (Zr, Mg, Al-based), and IXEPLAS-B1 (Zr, Bi-based) (all manufactured by Toagosei Co., Ltd.).
[0049] The inorganic ion scavenger may be in a powder form. When the inorganic ion scavenger is in a powder form, the average particle size of the inorganic ion scavenger may be 0.05 μm or more, 0.1 μm or more, 0.15 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, or 0.5 μm or more, and may be 10 μm or less, 5 μm or less, 3 μm or less, 2 μm or less, 1.5 μm or less, or 1 μm or less. The average particle size of the inorganic ion scavenger may be 0.05 to 10 μm. The average particle size of the inorganic ion scavenger can be measured by a laser diffraction / scattering method.
[0050] The content of the inorganic ion scavenger containing at least one selected from the group consisting of Al, Mg, Bi, Zr, Sb, and Zn may be 80 mass% or more, 90 mass% or more, or 95 mass% or more, based on the total mass of the inorganic ion scavenger. The content of the inorganic ion scavenger containing at least one selected from the group consisting of Al, Mg, Bi, Zr, Sb, and Zn may be substantially 100 mass% based on the total mass of the inorganic ion scavenger.
[0051] The content of the inorganic ion scavenger is 0.1 to 50% by mass relative to the total amount of the thermosetting resin. From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature (150°C) conditions and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulation reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85%RH) conditions, the content of the inorganic ion scavenger may be 0.3% by mass or more, 0.5% by mass or more, 1% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, or 10% by mass or more, and may be 40% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, or 15% by mass or less, relative to the total amount of the thermosetting resin.
[0052] From the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature and high humidity (85°C, 85% RH) conditions, the content of the inorganic ion scavenger may be 0.05 mass% or more, 0.1 mass% or more, 0.5 mass% or more, 1 mass% or more, 1.2 mass% or more, or 1.4 mass% or more, or may be 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, 8 mass% or less, 6 mass% or less, or 4 mass% or less, relative to the total mass of the resin composition.
[0053] The mass ratio of the inorganic ion scavenger to the copolymer (the content based on the mass of the inorganic ion scavenger / the content based on the mass of the copolymer) may be 0.005 or more, 0.01 or more, or 0.05 or more, and may be 1000 or less, 100 or less, or 50 or less, from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under a high temperature (150°C) condition, and from the viewpoint of easily obtaining a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under a high temperature and high humidity (85°C, 85%RH) condition. The mass ratio of the inorganic ion scavenger to the copolymer may be 25 or less, 10 or less, 5 or less, or 3 or less. The mass ratio of the inorganic ion scavenger to the copolymer may be 0.001 to 10000.
[0054] The resin composition may further contain a dispersant for dispersing the inorganic filler. The dispersant may be a copolymer having a (meth)acrylic monomer unit A having an anionic group (hereinafter also referred to as "unit A", and a monomer that gives unit A is also referred to as "monomer A"), a (meth)acrylic monomer unit B having a cationic group (hereinafter also referred to as "unit B", and a monomer that gives unit B is also referred to as "monomer B"), and a (meth)acrylic monomer unit C other than the (meth)acrylic monomer unit A and the (meth)acrylic monomer unit B (hereinafter also referred to as "unit C", and a monomer that gives unit C is also referred to as "monomer C"). The copolymer may have a (meth)acrylic monomer unit (unit X) having both an anionic group and a cationic group. In this case, unit X is considered to correspond to unit A and unit B. In other words, a copolymer having unit X is considered to have both unit A and unit B.
[0055] In this specification, "monomer" means a monomer having a polymerizable group before polymerization. "Monomer unit" means a structural unit derived from the monomer and constituting a copolymer. "(Meth)acrylic monomer" means a monomer having a (meth)acryloyl group. "(Meth)acrylic monomer" means an acrylic monomer and the corresponding methacrylic monomer, and similar expressions such as "(meth)acryloyl group" have the same meaning.
[0056] The copolymer has one or more types of each of the units A, B, and C. The copolymer may be a random copolymer or a block copolymer. The monomer A, B, and C may each be a monomer having one (meth)acryloyl group (monofunctional (meth)acrylic monomer), or a monomer having two or more (meth)acryloyl groups (polyfunctional (meth)acrylic monomer), and are preferably monofunctional (meth)acrylic monomers.
[0057] The anionic group contained in the unit A is, for example, one or more selected from the group consisting of a carboxyl group, a phosphoric acid group, a phenolic hydroxyl group, and a sulfonic acid group. From the viewpoint of further improving the dispersibility of the inorganic filler, the anionic group is preferably one or more selected from the group consisting of a carboxyl group, a phosphoric acid group, and a phenolic hydroxyl group.
[0058] From the viewpoint of further improving the dispersibility of the inorganic filler, the unit A preferably further has an electron-withdrawing group bonded to the anionic group. The electron-withdrawing group has the effect of stabilizing the anion of the anionic group. Examples of the electron-withdrawing group include a halogen group (also called a halogeno group). Examples of the anionic group bonded to an electron-withdrawing group include a group in which a halogen group is bonded to the carbon atom at the α-position of a carboxyl group.
[0059] The unit A may not have an electron donating group bonded to the anionic group. The electron donating group may destabilize the anion of the anionic group. An example of the electron donating group is a methyl group.
[0060] Examples of the monomer A include acrylic acid, methacrylic acid, acid phosphoxypropyl methacrylate, acid phosphoxypolyoxyethylene glycol monomethacrylate, acid phosphoxypolyoxypropylene glycol monomethacrylate, phosphoric acid modified epoxy acrylate, 2-acryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, 4-hydroxyphenyl acrylate, 4-hydroxyphenyl methacrylate, 2-methacryloyloxyethyl succinic acid, 2-acrylamido-2-methylpropanesulfonic acid, etc. From the viewpoint of further improving the dispersibility of the inorganic filler, the monomer A is preferably one or more selected from the group consisting of acrylic acid, 2-methacryloyloxyethyl phosphate, 4-hydroxyphenyl methacrylate, and 2-acrylamido-2-methylpropanesulfonic acid, more preferably acrylic acid.
[0061] The cationic group contained in the unit B is, for example, one or more selected from the group consisting of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium salt group. From the viewpoint of further improving the dispersibility of the inorganic filler, the cationic group is preferably a tertiary amino group.
[0062] From the viewpoint of further improving the dispersibility of the inorganic filler, the unit B preferably further has an electron donating group bonded to the cationic group. The electron donating group has the effect of stabilizing the cation of the cationic group. An example of the electron donating group is a methyl group. An example of the cationic group bonded to an electron donating group is a group in which a methyl group is bonded to the carbon atom at the α position of an amino group.
[0063] The unit B may not have an electron-withdrawing group bonded to the cationic group. The electron-withdrawing group may destabilize the cation of the cationic group. An example of the electron-withdrawing group is a carboxyl group.
[0064] Examples of the monomer B include 1-aminoethyl acrylate, 1-aminopropyl acrylate, 1-aminoethyl methacrylate, 1-aminopropyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, t-butylaminoethyl (meth)acrylate, dimethylaminoethyl methacrylate quaternary salt, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, dimethylaminoethyl acrylate benzyl chloride quaternary salt, etc. From the viewpoint of further improving the dispersibility of the inorganic filler, the monomer B is preferably one or more selected from the group consisting of 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate and 2,2,6,6-tetramethyl-4-piperidyl methacrylate, more preferably 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate.
[0065] The unit C is a (meth)acrylic monomer that does not contain either a cationic group or an anionic group. The unit C may have an amphipathic group, a hydrophobic group, or a hydrophilic group in addition to a (meth)acryloyl group. Examples of the amphipathic group include an oxyalkylene group. Examples of the hydrophobic group include a siloxane group and a hydrocarbon group. Examples of the hydrophilic group include a phosphate ester group. Note that the hydrocarbon group here does not include a methyl group constituting a methacryloyl group (hereinafter, the same applies to the hydrocarbon group in the unit C).
[0066] From the viewpoint of affinity or compatibility between the copolymer and the resin when the resin composition further contains a resin, the unit C has one or more selected from the group consisting of an oxyalkylene group, a siloxane group, and a hydrocarbon group, and more preferably has one or more selected from the group consisting of a siloxane group and a hydrocarbon group.
[0067] Examples of the (meth)acrylic monomer having an oxyalkylene group include ethoxycarbonylmethyl (meth)acrylate, phenol ethylene oxide modified (meth)acrylate, phenol (ethylene oxide 2 mol modified) (meth)acrylate, phenol (ethylene oxide 4 mol modified) (meth)acrylate, paracumylphenol ethylene oxide modified (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, nonylphenol (ethylene oxide 4 mol modified) (meth)acrylate, nonylphenol (ethylene oxide 8 mol modified) (meth)acrylate, nonylphenol (propylene oxide 2.5 mol modified) acrylate, 2-ethylhexylcarbitol (meth)acrylate, ethylene oxide modified phthalic acid (meth)acrylate, ethylene oxide modified succinic acid (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate.
[0068] Examples of (meth)acrylic monomers having siloxane groups include α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane. Examples of (meth)acrylic monomers having hydrocarbon groups include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, phenyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, and methoxylated cyclodecatriene (meth)acrylate.
[0069] An example of the (meth)acrylic monomer having a phosphate group is (meth)acryloyloxyethyl dialkyl phosphate.
[0070] In addition to the above, the monomer C may be, for example, a (meth)acrylic monomer having a hydroxy group. Examples of the (meth)acrylic monomer having a hydroxy group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate.
[0071] Monomer C may be, for example, a (meth)acrylic monomer having an amide bond. Examples of the (meth)acrylic monomer having an amide bond include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, diacetone(meth)acrylamide, and acryloylmorpholine.
[0072] Monomer C may be, for example, a polyfunctional (meth)acrylic monomer. Examples of polyfunctional (meth)acrylic monomers include 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexadiol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, 2-ethyl-2-butyl-propanediol (meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, 2-(1,2-cyclohexacarboximide)ethyl (meth)acrylate, hexanediol di(meth)acrylate, and polyfunctional (meth)acrylate having a bisphenol structure.
[0073] The content of the unit A may be 0.03 mol% or more, 0.1 mol% or more, 0.5 mol% or more, 1 mol% or more, 2 mol% or more, 3 mol% or more, 4 mol% or more, or 5 mol% or more, or 70 mol% or less, 60 mol% or less, 50 mol% or less, 40 mol% or less, 30 mol% or less, 20 mol% or less, 15 mol% or less, 10 mol% or less, or 5 mol% or less, relative to 100 mol% of the total of the unit A, the unit B, and the unit C (in other words, the total of all monomer units contained in the copolymer. The same applies below). When the content of the unit A is 0.03 mol% or more, the dispersibility of the inorganic filler tends to be further improved. When the content of the unit A is 70 mol% or less, the viscosity of the resin composition is further reduced, and the handleability of the resin composition tends to be further improved.
[0074] The content of the unit B may be 0.02 mol% or more, 0.05 mol% or more, 0.07 mol% or more, or 0.1 mol% or more, or 20 mol% or less, 10 mol% or less, 5 mol% or less, 3 mol% or less, 1 mol% or less, 0.5 mol% or less, or 0.1 mol% or less, based on the total 100 mol% of the unit A, the unit B, and the unit C. When the content of the unit B is 0.02 mol% or more, the affinity of the copolymer to the inorganic filler tends to be better. When the content of the unit B is 20 mol% or less, the viscosity of the resin composition tends to be lowered, and the handleability of the resin composition tends to be improved.
[0075] The content of the unit C may be 10 mol% or more, 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, 90 mol% or more, 92 mol% or more, or 94 mol% or more, or 99.8 mol% or less, 99 mol% or less, 98 mol% or less, 97 mol% or less, 96 mol% or less, or 95 mol% or less, based on the total 100 mol% of the unit A, the unit B, and the unit C. When the content of the unit C is 10 mol% or more, the viscosity of the resin composition is further reduced, and the handleability of the resin composition tends to be further improved. When the content of the unit C is 99.8 mol% or less, the affinity of the copolymer to the inorganic filler tends to be better.
[0076] The total content of the unit A and the unit B may be 0.05 mol% or more, 0.2 mol% or more, 1 mol% or more, 2 mol% or more, 3 mol% or more, 4 mol% or more, or 5 mol% or more, or 90 mol% or less, 80 mol% or less, 70 mol% or less, 60 mol% or less, 50 mol% or less, 40 mol% or less, 30 mol% or less, 20 mol% or less, 10 mol% or less, 8 mol% or less, or 6 mol% or less, relative to the total content of the unit A, the unit B, and the unit C (100 mol%). When the total content of the unit A and the unit B is 0.05 mol% or more, the dispersibility of the inorganic filler tends to be further improved. When the total content of the unit A and the unit B is 90 mol% or less, the handleability of the resin composition tends to be further improved.
[0077] The molar ratio of unit A to unit B (unit A / unit B) may be 0.01 or more, 0.9 or more, 1 or more, 5 or more, 10 or more, 20 or more, 30 or more, 40 or more, or 50 or more, and may be 200 or less, 150 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, 15 or less, or 10 or less. When the molar ratio of unit A to unit B is within the above range, the dispersibility of the inorganic filler tends to be further improved.
[0078] The weight average molecular weight of the copolymer may be 1,000 or more, 5,000 or more, 7,000 or more, 10,000 or more, 20,000 or more, 30,000 or more, 40,000 or more, or 50,000 or more, or 1,000,000 or less, 500,000 or less, 300,000 or less, 100,000 or less, 90,000 or less, 80,000 or less, 70,000 or less, or 60,000 or less. By having a weight average molecular weight of the copolymer of 1,000 or more, even if the resin composition is stored for a long time under a high temperature environment, the dispersibility of the inorganic filler can be maintained and the hardness increase of the resin composition can be suppressed. In addition, the shape retention of the resin composition is improved, and when applied to a sloping or vertical surface, the shifting or dripping of the resin composition is suppressed. By making the weight-average molecular weight of the copolymer 1,000,000 or less, the viscosity of the resin composition is further reduced, and the handleability of the resin composition tends to be further improved. The weight-average molecular weight of the copolymer is determined as the weight-average molecular weight converted into standard polystyrene using a GPC (gel permeation chromatography) method.
[0079] The copolymer is obtained by polymerizing the monomer A, the monomer B, and the monomer C by a known polymerization method. Examples of the polymerization method include radical polymerization and anionic polymerization. The polymerization method is preferably radical polymerization.
[0080] The polymerization initiator used in the radical polymerization may be a thermal polymerization initiator or a photopolymerization initiator. Examples of the thermal polymerization initiator include azo compounds such as azobisisobutyronitrile; and organic peroxides such as benzoyl peroxide, tert-butyl hydroperoxide, and di-tert-butyl peroxide. Examples of the photopolymerization initiator include benzoin derivatives. The polymerization initiator may be a known polymerization initiator used in living radical polymerization such as ATRP and RAFT.
[0081] The polymerization conditions can be appropriately adjusted depending on the type of monomer, polymerization initiator, etc. When the copolymer is a random copolymer, each monomer may be mixed in advance and polymerized. When the copolymer is a block copolymer, each monomer may be added sequentially to the polymerization system.
[0082] The content of the copolymer may be 0.01 to 10 parts by mass relative to 100 parts by mass of the inorganic filler. By having the content of the copolymer within this range, it becomes easier to obtain a resin composition capable of forming an insulating layer having superior insulating reliability against application of a high DC voltage under high temperature (150°C) conditions. The content of the copolymer may be 0.05 parts by mass or more, 0.1 parts by mass or more, 0.5 parts by mass or more, 1 part by mass or more, 2 parts by mass or more, 3 parts by mass or more, or 4 parts by mass or more relative to 100 parts by mass of the inorganic filler, and may be 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, 5 parts by mass or less, or 4 parts by mass or less.
[0083] The content of the copolymer may be 0.1 mass% or more, 0.5 mass% or more, 1 mass% or more, 2 mass% or more, or 2.5 mass% or more, and may be 10 mass% or less, 8 mass% or less, 6 mass% or less, 5 mass% or less, 4 mass% or less, or 3 mass% or less, relative to the total mass of the resin composition.
[0084] The resin composition may further contain a curing agent for curing the thermosetting resin. The curing agent is appropriately selected according to the type of the thermosetting resin. For example, when the thermosetting resin is an epoxy resin, the curing agent may be an amine-based resin, an acid anhydride-based resin, or a phenol-based resin. The curing agent may be used alone or in combination of two or more kinds.
[0085] The content of the curing agent may be 1 mass % or more, or 3 mass % or more, and may be 10 mass % or less, or 5 mass % or less, based on the total mass of the resin composition.
[0086] The resin composition may further contain other components, such as a curing accelerator, a coupling agent, a leveling agent, an antioxidant, a defoaming agent, a wetting agent, a dispersant, and a stabilizer.
[0087] The resin composition is obtained by mixing a thermosetting resin, an inorganic filler, and an inorganic ion scavenger (and further a dispersant, a curing agent, and other components used as necessary). The mixing may be performed using, for example, a planetary mixer, a universal mixer, a kneader, a hybrid mixer, or the like.
[0088] The resin composition may have a peak in the range of 2θ=11 to 15° in X-ray diffraction measurement. The peak position in X-ray diffraction measurement of the resin composition can be confirmed, for example, by preparing a cured product of the resin composition and subjecting the cured product to X-ray diffraction measurement. The resin composition may have a peak at a position of 2θ=11.5 to 14.5 or 11.8 to 14 in X-ray diffraction measurement.
[0089] The resin composition described above can be prepared by mixing a thermosetting resin, an inorganic filler, an inorganic ion scavenger, and other components as necessary. The resin composition may be prepared by mixing a powder containing at least scaly particles (first particles) and aggregated particles (second particles) of the scaly particles as the inorganic filler with components other than the inorganic filler, or by preparing a powder containing the first particles and a powder containing the second particles, respectively, and then mixing these powders with components other than the inorganic filler.
[0090] The resin composition can be used, for example, after curing. That is, one embodiment of the present invention is a cured product (insulating resin cured product) of the above-mentioned resin composition. The cured product may be in a semi-cured state (B stage) or a completely cured state (C stage).
[0091] The cured product can be obtained, for example, by subjecting the above-mentioned resin composition to heat treatment to cure it. The conditions of the heat treatment (heating temperature, heating time, etc.) are appropriately set depending on the types of resin and curing agent, the desired cured state, etc. The heat treatment may be performed in one step or two steps.
[0092] The cured product may be, for example, in the form of a sheet. The sheet-shaped cured product may be obtained, for example, by applying the above-mentioned resin composition onto a substrate and heating (and pressing as necessary). The sheet-shaped cured product may be a semi-cured B-stage sheet or a completely cured C-stage sheet.
[0093] The above-mentioned resin composition and its cured product are preferably used for forming an insulating layer of a metal base substrate. That is, the above-mentioned resin composition and its cured product can be called a resin composition for metal base substrates and a cured product for metal base substrates, respectively.
[0094] Fig. 1 is a schematic cross-sectional view showing one embodiment of a laminate. As shown in Fig. 1, a laminate 10A according to one embodiment includes a first metal layer 1A, an insulating layer (a cured product of the above-mentioned resin composition) 2 arranged on one surface of the first metal layer, and a second metal layer 3A arranged on the surface of the insulating layer 2 opposite to the first metal layer. In this laminate 10A, the first metal layer 1A and the second metal layer 3A are separated by the insulating layer 2 and are electrically insulated from each other.
[0095] Examples of metal materials constituting the first metal layer 1A include aluminum, aluminum alloys, copper, copper alloys, iron, and stainless steel. The first metal layer 1A may be made of one type of metal material, or may be made of two or more types of metal materials. The first metal layer 1A may have a single-layer structure or a multi-layer structure.
[0096] Examples of metal materials constituting the second metal layer 3A include copper, aluminum, and nickel. The second metal layer 3A may be made of one type of metal material, or may be made of two or more types of metal materials. The second metal layer 3A may have a single-layer structure or a multi-layer structure. In FIG. 1, the second metal layer 3A is disposed on substantially the entire surface of the insulating layer 2, but the second metal layer may be disposed only on a portion of the insulating layer 2.
[0097] The thickness of the first metal layer 1A may be, for example, 0.5 mm or more and 3 mm or less. The thickness of the insulating layer 2 may be, for example, 50 μm or more and 300 μm or less. The thickness of the second metal layer 3A may be, for example, 5 μm or more and 1 mm or less.
[0098] Fig. 2 is a schematic cross-sectional view showing one embodiment of a circuit board. As shown in Fig. 2, a circuit board 10B according to one embodiment includes a metal layer 1B, an insulating layer (a cured product of the above-mentioned resin composition) 2 arranged on one surface of the metal layer 1B, and a metal circuit section 3B arranged on the surface of the insulating layer 2 opposite to the metal layer 1B. In this circuit board 10B, the metal circuit section 3B is, for example, a circuit processed (e.g., etched) into a predetermined pattern.
[0099] Examples of the metal material constituting the metal layer 1B include the same metal material as that constituting the first metal layer 1A. Examples of the metal material constituting the metal circuit portion 3B include the same metal material as that constituting the second metal layer 3A.
[0100] The thickness of the metal layer 1B may be, for example, 0.5 mm or more and 3 mm or less. The thickness of the insulating layer 2 may be, for example, 50 μm or more and 300 μm or less. The thickness of the metal circuit portion 3B may be, for example, 5 μm or more and 1 mm or less. EXAMPLES
[0101] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0102] <Synthesis of copolymer> The monomers used in the synthesis of the copolymers of the examples are shown below. ((Meth)acrylic monomer A having an anionic group) Acrylic acid (manufactured by Toagosei Co., Ltd.) ((Meth)acrylic monomer B having a cationic group) 1,2,2,6,6-Pentamethyl-4-piperidyl methacrylate (ADEKA CORPORATION "ADEKA STAB LA-82") ((Meth)acrylic monomer C) Benzyl methacrylate ("Light Ester BZ" manufactured by Kyoeisha Chemical Co., Ltd.)
[0103] First, 100 parts by mass of (meth)acrylic monomer consisting of 5 mol% acrylic acid, 0.1 mol% 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, and 94.9 mol% benzyl methacrylate were added to an autoclave equipped with a stirrer. Next, 0.5 parts by mass (relative to 100 parts by mass of the total of (meth)acrylic monomers) of azobisisobutyronitrile (manufactured by Tokyo Chemical Industry Co., Ltd.) as an initiator and 1000 parts by mass of a mixed solution of toluene (special grade reagent) and 2-propanol (special grade reagent) (toluene:2-propanol = 7:3 (volume ratio)) as a solvent were added, and the inside of the autoclave was replaced with nitrogen. After that, the autoclave was heated at 65 ° C in an oil bath for 20 hours to carry out radical polymerization. After the polymerization was completed, the mixture was degassed at 120 ° C under reduced pressure for 1 hour to obtain a copolymer.
[0104] The polymerization rate was 98% or more when analyzed by gas chromatography based on 100% of the monomer charge, which suggested that the ratio of each monomer unit in the copolymer was approximately the same as the monomer charge ratio.
[0105] The weight average molecular weight of the resulting copolymer was determined as a weight average molecular weight converted into standard polystyrene by using a GPC (gel permeation chromatography) method under the following measurement conditions. High-speed GPC equipment: Tosoh Corporation "HLC-8020" Columns: One Tosoh "TSK guardcolumn MP(xL)" 6.0mmID x 4.0cm, and two Tosoh "TSK-GELMULTIPOREHXL-M" 7.8mmID x 30.0cm (16,000 theoretical plates), for a total of three (total theoretical plate count: 32,000) Developing solvent: Tetrahydrofuran Detector: RI (Differential Refractometer)
[0106] <Preparation of Resin Composition> Example 1 27.9 parts by mass of naphthalene type epoxy resin HP-4032D (manufactured by DIC Corporation) as a thermosetting resin and 3.5 parts by mass of phenol novolac resin VH-4150 (manufactured by DIC Corporation) as a curing agent were stirred at 170 ° C. to dissolve the curing agent in the thermosetting resin. The resin in which the curing agent was dissolved, 12.9 parts by mass (10 vol%) of boron nitride filler (thermal conductivity 150 W / m · K) as an inorganic filler, 2.6 parts by mass (4phf) of copolymer, 1.3 parts by mass (4.5phr) of inorganic ion scavenger 1 (both ion exchangers (Zr, Mg, Al type), average particle size 0.2 μm, manufactured by Toagosei Co., Ltd.) as an inorganic ion scavenger, and 0.2 parts by mass of 1B2PZ (manufactured by Shikoku Kasei Co., Ltd.) as a curing accelerator were stirred and mixed for 15 minutes with a planetary mixer to prepare a resin composition. The inorganic filler was a powder consisting of 11.8 volume% scaly boron nitride particles (first particles, average particle size: 10.1 μm, average aspect ratio: 7.5, peak intensity ratio I(002) / I(100): 126.4) and 88.2 volume% agglomerated particles of scaly boron nitride particles (second particles, average particle size: 50.9 μm, average aspect ratio: 1.46, peak intensity ratio I(002) / I(100): 6.8), with peaks at 6.6 μm and 43.5 μm in the particle size distribution curve.
[0107] <Preparation of hardened body> The obtained resin composition was applied onto a 0.038 mm thick polyethylene terephthalate (PET) film so that the thickness after curing would be 0.20 mm, and then heated and dried at 100°C for 50 minutes, thereby producing a semi-cured product (a sheet in a B-stage state).
[0108] <Preparation of metal-based circuit board> The cured product (sheet in B-stage state) was peeled off from the PET film and placed on the roughened surface of a metal plate (copper plate with a thickness of 2.0 mm). The roughened surface of metal foil (copper foil with a thickness of 0.5 mm) was then placed on top of the cured product. The product was then heated and cured at 180°C for 410 minutes while applying a surface pressure of 10 MPa using a press.
[0109] Next, after masking predetermined positions with an etching resist, the copper foil was etched using a sulfuric acid-hydrogen peroxide mixed solution as an etching solution. The etching resist was removed, and the substrate was washed and dried to obtain a metal base circuit board having a circular electrode (copper foil) with a diameter of 20 mm.
[0110] Example 2 A resin composition, a cured body, and a metal base circuit board were prepared in the same manner as in Example 1, except that inorganic ion scavenger 2 (a dual ion exchanger (Zr, Bi type), average particle size 0.4 μm, manufactured by Toagosei Co., Ltd.) was used as the inorganic ion scavenger.
[0111] Example 3 A resin composition, a cured body, and a metal base circuit board were prepared in the same manner as in Example 1, except that inorganic ion scavenger 3 (anion exchanger (Mg, Al-based), average particle size 1.5 μm, manufactured by Toagosei Co., Ltd.) was used as the inorganic ion scavenger.
[0112] Example 4 A resin composition, a cured body, and a metal base circuit board were prepared in the same manner as in Example 1, except that inorganic ion scavenger 4 (anion exchanger (Bi-based), average particle size 1.5 μm, manufactured by Toagosei Co., Ltd.) was used as the inorganic ion scavenger.
[0113] Example 5 A resin composition, a cured body, and a metal base circuit board were prepared in the same manner as in Example 1, except that inorganic ion scavenger 5 (cation exchanger (Zr-based), average particle size 1.0 μm, manufactured by Toagosei Co., Ltd.) was used as the inorganic ion scavenger.
[0114] Example 6 A resin composition, a cured body, and a metal base circuit board were prepared in the same manner as in Example 1, except that inorganic ion scavenger 6 (two ion exchangers (Sb, Bi type), average particle size 1.0 μm, manufactured by Toagosei Co., Ltd.) was used as the inorganic ion scavenger.
[0115] Example 7 A resin composition, a cured body, and a metal base circuit board were prepared in the same manner as in Example 1, except that inorganic ion scavenger 6 (a dual ion exchanger (Zr, Bi-based), average particle size 1.5 μm, manufactured by Toagosei Co., Ltd.) was used as the inorganic ion scavenger.
[0116] Example 8 A resin composition, a cured body, and a metal-based circuit board were prepared in the same manner as in Example 1, except that the inorganic filler used was a powder consisting of 6.3 volume % scaly boron nitride particles (first particles, average particle size: 10.1 μm, average aspect ratio: 7.5, peak intensity ratio I(002) / I(100): 126.4) and 93.7 volume % agglomerated particles of scaly boron nitride particles (second particles, average particle size: 50.9 μm, average aspect ratio: 1.46, peak intensity ratio I(002) / I(100): 6.8), and had peaks at 6.6 μm and 43.5 μm in the particle size distribution curve.
[0117] Example 9 A resin composition, a cured body, and a metal-based circuit board were prepared in the same manner as in Example 1, except that the inorganic filler used was a powder consisting of 55.3 volume% scaly boron nitride particles (first particles, average particle size: 10.1 μm, average aspect ratio: 7.5, peak intensity ratio I(002) / I(100): 126.4) and 44.7 volume% agglomerated particles of scaly boron nitride particles (second particles, average particle size: 50.9 μm, average aspect ratio: 1.46, peak intensity ratio I(002) / I(100): 6.8), and had peaks at 6.6 μm and 43.5 μm in the particle size distribution curve.
[0118] Example 10 A resin composition, a cured product, and a metal base circuit board were prepared in the same manner as in Example 1, except that the amount of the inorganic ion scavenger was 0.14 parts by mass (0.5 phr).
[0119] Example 11 A resin composition, a cured product, and a metal base circuit board were prepared in the same manner as in Example 1, except that the amount of the inorganic ion scavenger was 0.42 parts by mass (1.5 phr).
[0120] Example 12 A resin composition, a cured product, and a metal base circuit board were prepared in the same manner as in Example 1, except that the amount of the inorganic ion scavenger was 1.8 parts by mass (6 phr).
[0121] (Example 13) A resin composition, a cured product, and a metal base circuit board were prepared in the same manner as in Example 1, except that the amount of the inorganic ion scavenger was 2.8 parts by mass (10 phr).
[0122] Example 14 A resin composition, a cured product, and a metal base circuit board were prepared in the same manner as in Example 1, except that the amount of the inorganic ion scavenger was 5.6 parts by mass (20 phr).
[0123] Comparative Example 1 A resin composition, a cured product, and a metal base circuit board were prepared in the same manner as in Example 1, except that no inorganic ion scavenger was added.
[0124] Comparative Example 2 A resin composition, a cured product, and a metal base circuit board were prepared in the same manner as in Example 1, except that the amount of the inorganic ion scavenger was 27.9 parts by mass (100 phr).
[0125] Comparative Example 3 A resin composition, a cured body, and a metal-based circuit board were prepared in the same manner as in Example 1, except that the inorganic filler used was a powder consisting of 0.9 volume % agglomerated particles of scaly boron nitride particles (first particles, average particle size: 50.9 μm, average aspect ratio: 1.46, peak intensity ratio I(002) / I(100): 6.8) and 99.1 volume % agglomerated particles of scaly boron nitride particles (second particles, average particle size: 50.9 μm, average aspect ratio: 1.46, peak intensity ratio I(002) / I(100): 6.8), and had peaks at 6.6 μm and 43.5 μm in the particle size distribution curve.
[0126] Comparative Example 4 A resin composition, a cured body, and a metal-based circuit board were prepared in the same manner as in Example 1, except that the inorganic filler used was a powder consisting of 77.1 volume % scaly boron nitride particles (first particles, average particle size: 10.1 μm, average aspect ratio: 7.5, peak intensity ratio I(002) / I(100): 126.4) and 22.9 volume % agglomerated particles of scaly boron nitride particles (second particles, average particle size: 50.9 μm, average aspect ratio: 1.46, peak intensity ratio I(002) / I(100): 6.8), and had peaks at 6.6 μm and 43.5 μm in the particle size distribution curve.
[0127] [Measurement of particle size distribution] The particle size distribution was measured under the following measurement conditions using a particle size distribution / particle shape analyzer (Microtrac, SYNC-3L S / N: H0153). The particle size distribution was measured by replacing the circulation bath with an aqueous solution of sodium hexametaphosphate, placing the sample in the circulation bath, and allowing it to stabilize before measuring. <Measurement conditions> Particle refractive index: 1.74 Particle shape: non-spherical Solvent used: Sodium hexametaphosphate aqueous solution Solvent refractive index: 1.333 Flow rate: 60% Measurement time: 10 seconds (wet)
[0128] [Measurement of average particle size and average aspect ratio] For the scaly boron nitride particles, the boron nitride particles were embedded in resin and mechanically polished and ion milled to prepare samples for cross-sectional observation. Gold plating was then applied to the prepared samples and the cross-sections were observed at 10,000x magnification using a scanning electron microscope (SEM). The maximum length and maximum thickness of 10 boron nitride particles in one field of view were measured, and the average particle diameter and average aspect ratio were calculated by calculating the average maximum length of each particle and the average maximum length / maximum thickness. For the agglomerated particles of scaly boron nitride particles, the particle size distribution was measured under the following measurement conditions using a particle size distribution / particle shape analyzer (Microtrac, SYNC-3L S / N: H0153). The average particle size and average aspect ratio were measured by replacing the circulation bath with an aqueous solution of sodium hexametaphosphate, placing the sample in the circulation bath and allowing it to stabilize before performing the measurements. <Measurement conditions> Particle refractive index: 1.74 Particle shape: non-spherical Solvent used: Sodium hexametaphosphate aqueous solution Solvent refractive index: 1.333 Measurement time: 10 seconds (wet)
[0129] [XRD peak measurement] X-ray diffraction measurements were performed on the cured bodies produced in each of the Examples and Comparative Examples using a Rigaku X-ray diffractometer, Rigaku MiniFlexII. The positions of the XRD peaks detected in the range of 2θ=11-15° are shown in Tables 1-4. The peak intensity ratio (I(002) / I(100)) of the boron nitride particles was measured in the range of 2θ=20-50°, and the intensity of the diffraction line near 2θ=27° was defined as I(002), and the intensity of the diffraction line near 2θ=41° was defined as I(100).
[0130] [Reliability evaluation by high-temperature and high-pressure bias test (Vt)] A high-temperature, high-voltage bias test (Vt) was conducted on the obtained metal base substrate, in which a DC voltage of 10 kV was applied between the metal foil and the metal plate in a 150°C environment to measure the time until dielectric breakdown. The time until dielectric breakdown was defined as the time from the start of voltage application to the point at which the leakage current value measured by a voltage resistance tester reached 10 mA or more. The measurement results are shown in Tables 1 to 4.
[0131] [Reliability evaluation using high temperature and humidity bias test (THB)] The obtained metal base substrate was subjected to a high temperature and humidity bias test (THB) in which a DC voltage of 2.0 kV was applied between the metal foil and metal plate in an environment of 85°C and 85% RH to measure the time until dielectric breakdown. The time until dielectric breakdown was defined as the time from the start of voltage application to the point at which the leakage current value measured by a voltage resistance tester reached 10 mA or more. The measurement results are shown in Tables 1 to 4. In the tables, "-" indicates that the measurement was not performed.
[0132] [Table 1]
[0133] [Table 2]
[0134] [Table 3]
[0135] [Table 4] [Explanation of symbols]
[0136] 1A...first metal layer, 1B...metal layer, 2...insulating layer, 3A...second metal layer, 3B...metal circuit portion, 10A...laminate, 10B...circuit board.
Claims
1. Contains a thermosetting resin, an inorganic filler, and an inorganic ion scavenger, the inorganic filler includes first particles which are scaly particles and second particles which are agglomerates of the scaly particles, a content of the first particles is 1 vol% or more and 60 vol% or less with respect to a total content of the first particles and the second particles, The content of the inorganic ion scavenger is 0.1 to 50 mass% based on the total amount of the thermosetting resin.
2. The resin composition according to claim 1, wherein the first particles have an average aspect ratio of 1 to 200, and the second particles have an average aspect ratio of 1 to 2.
3. the first particles are boron nitride particles, and in an X-ray diffraction measurement, a ratio I(002) / I(100) of a peak intensity I(002) of a (002) plane to a peak intensity I(100) of a (100) plane is 50 to 1000; The second particles are boron nitride particles, and the ratio I(002) / I(100) of the peak intensity I(002) of the (002) plane to the peak intensity I(100) of the (100) plane in X-ray diffraction measurement is 1 to 20. The resin composition according to claim 1.
4. The resin composition according to claim 1 , wherein a ratio of an average particle size of the first particles to an average particle size of the second particles is 1.5 or more and 20 or less.
5. The resin composition according to claim 1 , wherein a ratio of an average aspect ratio of the first particles to an average aspect ratio of the second particles is 0.01 or more and 0.8 or less.
6. The resin composition according to claim 1 , wherein the inorganic filler has a thermal conductivity of 20 W / m·K or more.
7. The resin composition according to claim 1, wherein the content of the inorganic filler is 30 to 70% by volume based on the total volume of the resin composition.
8. The resin composition according to claim 1 , wherein the inorganic ion scavenger comprises both an anion exchanger and a cation exchanger, or both ion exchangers.
9. The resin composition according to claim 1 , wherein the inorganic ion scavenger contains at least one selected from the group consisting of Al, Mg, Bi, Zr, Sb, and Zn.
10. The resin composition according to claim 1 , wherein the inorganic ion scavenger comprises at least one selected from the group consisting of Bi, Zr, Sb, and Zn.
11. The resin composition according to claim 1, which has a peak in the range of 2θ=11 to 15° in X-ray diffraction measurement.
12. The resin composition according to claim 1 , wherein the thermosetting resin is an epoxy resin.
13. Further comprising a copolymer, The resin composition according to claim 1, wherein the copolymer has (meth)acrylic monomer units A having an anionic group, (meth)acrylic monomer units B having a cationic group, and (meth)acrylic monomer units C other than the (meth)acrylic monomer units A and the (meth)acrylic monomer units B.
14. An insulating resin cured product, which is a cured product of the resin composition according to any one of claims 1 to 13.
15. a first metal layer, an insulating layer disposed on one surface of the first metal layer, and a second metal layer disposed on a surface of the insulating layer opposite to the first metal layer; A laminate, wherein the insulating layer is the insulating resin cured body according to claim 14.
16. a metal layer, an insulating layer disposed on one surface of the metal layer, and a metal circuit portion disposed on a surface of the insulating layer opposite to the metal layer; A circuit board, wherein the insulating layer is the insulating resin cured body according to claim 14.
Citation Information
Patent Citations
Method for constructing coke oven and temporary shed for constructing the coke oven
JP2008266533A